2013
DOI: 10.3109/00952990.2013.848876
|View full text |Cite
|
Sign up to set email alerts
|

Psychological dysregulation during adolescence mediates the association of parent-child attachment in childhood and substance use disorder in adulthood

Abstract: Objective This prospective study tested the hypothesis that psychological dysregulation in mid-adolescence (age 16) mediates the association between parent-child attachment in late childhood (age 10-12) and development of substance use disorder (SUD) in adulthood (age 22). Method The Youth Attachment to Parents Scale (YAPS) was developed in 10-12 year old boys and girls (N = 694) at baseline residing in western Pennsylvania. Psychological dysregulation was measured by the neurobehavior disinhibition trait. S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 49 publications
(59 reference statements)
0
6
0
Order By: Relevance
“…Danielsson et al (77) showed that attachment security at age 13 years prevented heavy drinking episodes at age 15 years. In a study by Zhai et al (76), insecure attachment at age 10 to 12 years led to dysregulation at age 16 years and substance abuse at age 22 years. In a meta-analytic calculation, Jordan and Sack (78) calculated that secure attachment decreases the risk for substance abuse by odds ratios ranging from 0.60 to 0.70.…”
Section: Resultsmentioning
confidence: 99%
“…Danielsson et al (77) showed that attachment security at age 13 years prevented heavy drinking episodes at age 15 years. In a study by Zhai et al (76), insecure attachment at age 10 to 12 years led to dysregulation at age 16 years and substance abuse at age 22 years. In a meta-analytic calculation, Jordan and Sack (78) calculated that secure attachment decreases the risk for substance abuse by odds ratios ranging from 0.60 to 0.70.…”
Section: Resultsmentioning
confidence: 99%
“…14 Supervisory neglect is parental failure to protect children from harmful situations or people, 1 which compromises familial bonding and may increase substance abuse among neglected youth. 15 On the other hand, families that are cohesive, warm, or bonded during childhood have been found to protect against substance use for young adults, 14 along with living with one's parents. 16,17 A serious romantic relationship may also protect against substance abuse.…”
Section: Introductionmentioning
confidence: 99%
“…Recent research suggests that psychological dysregulation during adolescence mediates the association of parent-child attachment in childhood and substance use disorder in adulthood (Zhai et al, 2014), but it is not clear to what extent psychological dysregulation contributes to the development of suicidal symptoms. Behavioral under control has also been suggested as a possible mechanism to explain substance use disorders and suicidal symptoms and the association between those symptoms Kelly et al, 2004; Groholt et al, 2000).…”
Section: Discussionmentioning
confidence: 99%